2004
DOI: 10.1016/s1043-951x(03)00029-4
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic interrelationships between the greater China share markets

Abstract: This paper investigates the interrelationships between prices on the mainland Chinese share market and those in the neighbouring markets of Hong Kong and Taiwan. While there is a growing literature on interrelationships between share market including the emerging markets in Asia, very little is known about the role of mainland markets in the region. We consider the interrelationships between the Shanghai and Shenzhen exchanges and those in Hong Kong and Taiwan. We begin by combining the Shanghai and Shenzhen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 31 publications
3
39
1
Order By: Relevance
“…Similar to the result by Chan and Lo (2000), found that there is a significant feedback relationship between the Shanghai and Shenzhen A markets. Evidence from their cointegration tests in Groenewold et al(2004) is consistent with that of who found cointegration between the two mainland A-share indices for the period before the Asian crisis, which disappeared after the crisis. They also found a strong but relatively isolated lead-lag relationship between the two mainland A-share markets.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Similar to the result by Chan and Lo (2000), found that there is a significant feedback relationship between the Shanghai and Shenzhen A markets. Evidence from their cointegration tests in Groenewold et al(2004) is consistent with that of who found cointegration between the two mainland A-share indices for the period before the Asian crisis, which disappeared after the crisis. They also found a strong but relatively isolated lead-lag relationship between the two mainland A-share markets.…”
supporting
confidence: 81%
“…2 China's stock exchanges started as relatively new players in the region just recent years and have expanded rapidly in terms of capitalization, turnover, and the number of firms listed since their establishment; with the result being China's stock market becoming the second largest in Asia, behind only Japan (Groenewold, et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the results of this study do not suggest there is any improvement in the A share market integration with the world markets even during the financial crisis period. This finding, to some extent, contradicts the argument of Groenewold, Tang and Wu (2004), who contend that the mainland market became more closely linked to the Hong Kong market after crisis by using vector-autoregressive models (VARs). The Hong Kong stock market, which is supposed to have a much closer relationship with the mainland, has little significance in the pricing of domestic stocks.…”
Section: Resultsmentioning
confidence: 71%
“…This is not only because the financial markets in this region have grown rapidly over the past decade, but also because of the arguably asymmetric integration of the emerging Chinese economy with advanced countries in the real side of the economy and tight control over financial market. These three markets have been Despite the growing importance of the greater China stock markets and their dynamic interactions, there are only a few studies on this issue (see Johansson and Ljungwall, 2006, Groenewold et al 2004, and Cheng and Glascock, 2005. In particular, Groenewold et al (2004) investigate the interrelationships between prices on the mainland Chinese share market and those in the neighboring markets of Hong Kong and Taiwan and find a strong contemporaneous relationship between the two mainland markets but that the mainland markets are relatively isolated from the other two markets considered.…”
Section: Introductionmentioning
confidence: 99%
“…These three markets have been Despite the growing importance of the greater China stock markets and their dynamic interactions, there are only a few studies on this issue (see Johansson and Ljungwall, 2006, Groenewold et al 2004, and Cheng and Glascock, 2005. In particular, Groenewold et al (2004) investigate the interrelationships between prices on the mainland Chinese share market and those in the neighboring markets of Hong Kong and Taiwan and find a strong contemporaneous relationship between the two mainland markets but that the mainland markets are relatively isolated from the other two markets considered. Also, both Hong Kong and Taiwan have strong contemporaneous relationships, a feature that is more marked after the Asian crisis.…”
Section: Introductionmentioning
confidence: 99%